(untitled) (Baghdad Science Journal, 2019)
Rice is a major staple food for more than two thirds of the world population. Pathogenesis-related proteins-10 (PR10) have a range of 154 to 163 amino acid with molecular weight 17 kDa. They are acidic and generally intracellular and cytosolic proteins accumulate in plants in response to biotic and abiotic stresses. In the present study, a PR10 gene and its corresponding protein were characterized in O. sativa, O. barthii, O. glaberrima, O. glumipatula, O. meridionalis, O. nivara, O. rufipogon and O. punctata. The results revealed a narrow range of variation at both DNA and protein levels in all examined species except O. glumipatula. The latter showed a relatively obvious structural variation at protein level. Such variation may be beneficial against different types of stress that requires further elucidation to exploit in rice breeding programs.